Midwives’ Experience of Traumatic Birth in Cyprus - Hadjigeorgiou, Eleni; Koliandri, Ioanna; Josephidou, Eva (My University, 2023)
In the twenty-first century, research evidence justifies that maternity health professionals, particularly midwives, may experience a birth as traumatic. Childbirth in Cyprus is highly medicalized and midwives as advocates of normal birth, face enormous difficulties to fulfill their professional role. Therefore, identified as crucial to finding more about midwives’ experience providing perinatal care in Cyprus. A study was carried out to explore midwives’ experiences of traumatic childbirth in Cyprus and how this affects their personal and professional life. Qualitative design approach was used based on Husserl’s phenomenological approach. Following ethical approval, data were collected through semi-structured interviews with a purposive sample of midwives (N = 14) from September until December 2021. Data were analyzed using Colaizzi’s method and analysis revealed three main themes with subthemes: (1) The nature of traumatic events, (2) Consequences of traumatic experience, and (3) Dealing with traumatic events. Some midwives become defensive and careful, in order to avoid a similar traumatic experience in the future, while some of them develop symptoms of post-traumatic stress disorder (PTSD). Midwives in Cyprus experience traumatic events during childbirth that negatively affect their professional and personal life with long-term effects. Collegiality is important to deal with traumatic events. More awareness must be created during basic and continuing education about decision-making power and problem-solving.
Keywords: Trauma; Midwives; Experiences; Midwifery care; Traumatic labor; Traumatic birth; Perceptions